Analysis of Fiscal Incentive Policies in The Electronic Industries Using Regulatory Impact Analysis (RIA) - Vierke, Intan Maria Lewiayu; Budhi, Dharma; Achmad Sanusi; Syaiful Ahmar (Kirana Publisher (KNPub), 2023)
As one of the sectors that are the focus of the development of Making Indonesia 4.0, the electronics industry is one of the sectors that must accelerate itself in facing high competition in the era of the industrial revolution 4.0, where the development of digital technology and global needs for various technology support instruments are very high. The competitiveness of the electronics industry must be a concern; for this reason, this research will analyse the fiscal incentives applied to the electronics industry sector, especially the Government Borne Import Duty (BMDTP). The implementation of RIA supports the policy-making process by including valuable empirical data for a policy decision and constructing a rational decision framework to examine the potential implications of regulatory policy choices. Based on the analysis conducted, the data shows that the BMDTP policy is to encourage the ease of importing raw materials that can increase industrial competitiveness; the application of the BMDTP policy is clear and understandable; only inconsistencies in the timing of its implementation, and the performance of the electronics sector industry shows the benefits of implementing the BMDTP policy.